Serum leptin concentration in young diabetics - Ismail, I.S.; Wan Mohamad, W.B.; Wan Nazaimoon, W.M.; Letchuman, R.; Hew, F.L.; Pendek, R.; Singaraveloo, M.; Faridah, I.; Sheriff, I.H.; Khalid, B.A.K. (ASEAN Federation of Endocrine Societies (AFES), 1999)
The objective of the study was to examine the serum leptin level in young diabetics (age of onset of diabetes <40 years old) and to determine its relationship with gender, body mass index (IBM), waist-hip ratio (WHR), type of diabetes, fasting (CF) and glucagon-stimulated C-peptide (CG). A total of 219 Type 1 (97 males, 122 females) and 423 Type 2 (216 males, 207 females) patients were recruited for the study. Blood was drawn for assays of C-peptide, leptin and glycosylated haemoglobin (HbAIc) after an overnight fast, and at 6 minutes after intravenous infusion of 1 mg glucagon for CG levels. The BMI was significantly higher in Type 2 than Type 1 diabetics (26.0±0.3 versus 22.4±0.6 kg/m2, p= 0.001). Males with Type 1 and Type 2 diabetes had significantly higher WHR compared to females. However, the serum leptin concentration was significantly higher in female subjects regardless of the type of diabetes (11.4±0.7 versus 5.4±0.5 ng/ml for Type 1 and 13.1±0.6 versus 7.8±0.4 ng/ml for Type 2) and BMI (10.7±0.7 versus 4.0±0.8 ng/ml for Type 1 diabetics and 10.8±0.6 versus 5.8±0.5 ng/ml for Type 2 diabetics with BMI _<25 kg/m², 15.5±0.2 versus 6.9±l.4 ng/ml for Type 1 and 16.2±1.0 versus 9.9±0.2 ng/ml for Type 2 diabetics with BMI >25 kglm2). Leptin concentration was positively correlated with BMI (r=0.410, p=0.0001 for Type 1; r=0.416, p=0.0001 for Type 2). The best independent predictors for serum leptin were BMI (female), age (Type 2 only ), WHR (Type 1 males and females only), CF (males only) and CG. This study confirmed that besides gender, BMI, WHR and C-peptide levels are also important factors in predicting serum leptin concentration in diabetics.